Sexual Harassment It's Not Academic. (Distributed by ERIC Clearinghouse, 1997)
Sexual harassment affects students at all levels of education. To combat this problem, fundamental information that can help school administrators, teachers, students, and parents recognize and deal with sexual harassment under Title IX are presented in this pamphlet. The text describes quid pro quo harassment and hostile-environment harassment, and outlines the basic principles of harassment in a question-and-answer format. These questions include: What are some examples of sexual conduct? Must sexual conduct be unwelcome in order to be sexual harassment? Does all sexual conduct create a sexually hostile environment? When does sexual conduct create a sexually hostile environment? What steps can a school take to prevent sexual harassment? What can a student do if he or she is confronted with sexual harassment? How should a school respond to information about alleged sexual harassment? What if the student who was harassed insists on confidentiality, or asks that the matter not be pursued? What should a school do if it determines that there has been sexual harassment? What should be included in a school's grievance procedures? What should a school do to publicize its policy against sexual harassment? and How does a student file a complaint to the Office of Civil Rights? (RJM)
ERIC Document Number: ED423609.
Availability: U.S. Department of Education, Office for Civil Rights, Customer Service Team, 330 C Street, S.W., Washington, DC 20202; Tel: 800-421-3481 (Toll Free).
ERIC Note: For the 1995 edition, see ED 402 856.
Also distributed on microfiche by U.S. GPO under ED 1.310/2:423609.
Keywords: Educational Environment.; Elementary Secondary Education.; Prevention.; School Policy.; School Security.; Sexual Abuse.; Sexual Harassment.